Obtenção de amido resistente por intercruzamento e por tratamento hidrotérmico, e sua incorporação em bolos - Moraes, Jaqueline de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Resistant starch (RS) is defined as starch, or starch fraction, which is not digested in the gastrointestinal tract and can be fermented in the colon performing similar functional properties to those of dietary fiber. The RS application in bakery products can increase the fiber content of these foods without causing major changes in their sensory characteristics, requiring minor adjustments in formulation due to lower water absorption of RS compared to traditional fibers. In this work banana, cassava, corn and potato starches have been modified by heat moisture treatment (HMT), and crosslinking to obtain RS and then apply it in cakes. The HMT was conducted in starch conditioned at 18, 20 and 35% moisture using heating (130 °C), cooling (4 °C) and freezing (-18 °C) cycles. The starches were cross-linked using a mixture of sodium trimetaphosphate and sodium tripolyphosphate (99:1) at 45 °C for different times. The structural characteristics of native and modified starches were studied using X-ray diffraction, 31P nuclear magnetic resonance (31P NMR), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). Pasting properties, phosphorus content and digestibility of starches were also determined. The modification of starches by HMT resulted in low RS content, which didn’t exceed 2.57% in gelatinized starches for all conditions used. The RS content of cross-linked starches increased reaching 88.66, 65.40, 60.08 and 43.56% for potato starch, cassava, banana and corn, respectively, with acceptable phosphorous content. The higher treatment time resulted in higher levels of phosphorus, reduction in starch rapidly digestible starch (RDS) and slowly digestible starch (LDS) contents and increase the RS content of all starches. However, starches of different botanical sources show different behavior during phosphorylation and different RS contents. The gelatinization temperature of crosslinked starches had small changes compared to native starches, but the crosslinked starches no showed viscosity peak when analyzed by Rapid Visco Analyzer, indicating the formation of covalent bonds which result in a rigid granular structure. The X-ray diffraction patterns did not change with crosslinking, although the relative crystallinity decreased in banana, potato and cassava starches and increased in corn starch. The inclusion of phosphate groups during the crosslinking, which initially occurs in the amorphous region of the granule, promotes swelling in this region and results in change in the crystalline region. The formation of different phosphate esters was observed in 31P NMR spectras, that showed great influence on digestibility of starch. Among such esters are the monostarch monophosphate (MSMP) distarch monophosphate (DSMP), monostarch diphosphate (MSDP) and the cyclic monostarch monophosphate (cyclic MSMP), which alter the digestibility by hindering access of enzymes due to the volume of the formed structures (MSMP, MSDP and cyclical MSMP) or by cross-link the chains (MSDP). The steric hindrance promoted by the inclusion of phosphate groups may be strongly related to the increase in the RS content of starches. The incorporated phosphorus content was found to have less influence than that the way the phosphorous is linked in the starch molecules to reduce enzymatic digestibility. The addition of RS in cakes resulted in products with higher volume, greater crumb clarity, and lower retrogradation, but the fiber content was lower than that for the cakes can be considered as a source of fiber.

Amido resistente (AR) é definido como o amido, ou fração de amido, que não é digerido no trato gastrointestinal e pode ser fermentado no cólon apresentando propriedades funcionais similares às das fibras alimentares. A aplicação de AR em produtos de panificação permite aumentar o teor de fibras desses alimentos sem provocar grandes alterações em suas características sensoriais demandando menores ajustes na formulação devido à menor absorção de água destes comparados às fibras tradicionais. Nesse trabalho amidos de banana, batata, mandioca e milho foram modificados por tratamento térmico a baixa umidade (TTBU), e por intercruzamento visando a obtenção de AR e sua aplicação em bolos. O TTBU foi aplicado aos amidos condicionados a 18, 20 e 35 % de umidade utilizando ciclos de aquecimento (130 ºC), resfriamento (4 ºC) e congelamento (-18 ºC). O intercruzamento foi realizado utilizando uma mistura de trimetafosfato de sódio e tripolifosfato de sódio (99:1) a 45 ºC durante diferentes tempos. As características estruturais dos amidos nativos e modificados foram estudadas usando difração de raios-X, ressonância magnética nuclear de 31P (31P RMN), microscopia eletrônica de varredura (MEV) e calorimetria explanatória diferencial (DSC). As propriedades de pasta, o teor de fósforo e digestibilidade dos amidos foram também determinados. A modificação dos amidos por TTBU resultou em baixos teores de AR que não ultrapassou 2,57% nos amidos gelatinizados em todas as condições testadas. O intercruzamento aumentou o teor de AR que atingiu 88,66, 65,40, 60,08, e 43,56 % nos amidos de batata, mandioca, banana e milho, respectivamente, com teores máximos de fósforo permitidos para aplicação em produtos alimentícios. O aumento no tempo de tratamento resultou em maiores teores de fósforo, redução nos teores de amido rapidamente digerível e amido lentamente digerível e aumento no teor de AR em todos os amidos. Porém os amidos de diferentes fontes botânicas apresentaram diferentes velocidades de incorporação de fósforo e diferentes teores de AR de acordo com o teor de fósforo incorporado. As temperaturas de gelatinização dos amidos intercruzados apresentaram pequenas variações em comparação aos amidos nativos, porém nenhum dos amidos modificados por intercruzamento apresentou pico de viscosidade quando analisado em Rápido Visco Analisador, indicando a formação de ligações covalentes que resultaram em uma estrutura granular rígida. Os padrões de difração de raios-X não foram modificados com o intercruzamento, porém a cristalinidade relativa dos amidos foi alterada, com redução nos amidos de banana, batata e mandioca e aumento no amido de milho. A inclusão dos grupamentos fosfato durante o intercruzamento, que acontece inicialmente na região amorfa dos grânulos, resulta no aumento do volume dessa região e consequente alteração na região cristalina. Os espectros obtidos por 31P RMN permitiram observar a formação de diferentes formas de ésteres de fosfato que mostraram grande influência na digestibilidade dos amidos. Entre esses ésteres estão o monoamido monofosfato (MSMP), diamido monofosfato (DSMP), monoamido difosfato (MSDP) e o monoamido monofosfato cíclico (ciclíco MSMP), os quais alteram a digestibilidade por dificultar o acesso das enzimas devido ao volume das estruturas formadas (MSMP, MSDP e cíclico MSMP) ou pelo intercruzamento das cadeias (MSDP). O impedimento estérico promovido pela inclusão dos grupos fosfatos pode estar fortemente relacionado ao aumento no teor de AR dos amidos. O teor de fósforo incorporado mostrou ter menor influência do que a forma como esse fósforo se liga as moléculas de amido para a redução da digestibilidade enzimática. A adição de AR em bolo inglês resultou em produtos com maior volume, maior claridade no miolo, e menor retrogradação, mas o teor de fibras obtido foi inferior ao necessário para que os bolos possam ser considerados como fonte de fibras.
Resistant starch production by crosslinking and hydrothermal treatment, and their incorporation into cakes
Keywords: Resistant starch; Crosslinked starch; Digestibility; Structure; Amido resistente; Amido intercruzado; Digestibilidade; Estrutura